2017
DOI: 10.1002/ep.12609
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric LiTaO3 as novel photo‐electrocatalyst in microbial fuel cells

Abstract: Microbial fuel cells (MFCs) are a promising technology for simultaneous electricity generation and wastewater treatment. Noble materials can offer high catalyst performance in MFCs but their high cost poses an obstacle for the practical implementation of this technology. Ferroelectric materials such as LiTaO 3 are a new generation of photocatalysts that could potentially be used for the oxygen reduction reaction in these devices. Thus, this work investigates the performance of LiTaO 3 as cathode catalyst in MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…This power value is 10 times greater than that of the MFC using the photocatalyst prepared by slow cooling, displaying a higher catalytic activity. [40] Compared with previous works, the power generated in the case of the Li 0.95 Ta 0.57 Nb 0.38 Cu 0.15 O 3 prepared by rapid cooling (205 mW/m 3 ) was 3.7 fold higher than that of the LiTaO 3 (55 mW/m 3 ), [33] and 1.6 fold higher than that of the LiNbO 3 , [43] indicating an important efficiency of the photocatalyst prepared by rapid cooling. [38] The smallest particles (11.24 mm) of the photocatalyst prepared by rapid cooling could also improve the catalytic properties compared with the photocatalyst prepared by slow cooling (42.60 mm) (see the PDS analysis).…”
Section: Psd Curvesmentioning
confidence: 70%
See 1 more Smart Citation
“…This power value is 10 times greater than that of the MFC using the photocatalyst prepared by slow cooling, displaying a higher catalytic activity. [40] Compared with previous works, the power generated in the case of the Li 0.95 Ta 0.57 Nb 0.38 Cu 0.15 O 3 prepared by rapid cooling (205 mW/m 3 ) was 3.7 fold higher than that of the LiTaO 3 (55 mW/m 3 ), [33] and 1.6 fold higher than that of the LiNbO 3 , [43] indicating an important efficiency of the photocatalyst prepared by rapid cooling. [38] The smallest particles (11.24 mm) of the photocatalyst prepared by rapid cooling could also improve the catalytic properties compared with the photocatalyst prepared by slow cooling (42.60 mm) (see the PDS analysis).…”
Section: Psd Curvesmentioning
confidence: 70%
“…[14] These materials are known by their catalytic performance for the oxygen reduction reaction, but they are too expensive and vulnerable to contaminations by compounds present in wastewater. [2,[31][32][33]39] In this work, a new photocatalytic material with the chemical formula Li 0.95 Ta 0.57 Nb 0.38 Cu 0.15 O 3 is studied as a cathode catalyst in microbial fuel cells. [19][20][21][22][23][24] These materials mentioned above are limited by their selectivities, stabilities, and catalytic activities.…”
mentioning
confidence: 99%
“…Another material used as photocathode is lithium-tantalate (LiTaO 3 ), which was also used as a photocathode in biological fuel cell application. When LiTaO 3 photocathode was illuminated with a 500 W of UV/Vis intensity, it can deliver 3-folds higher of power (55 mW cm −2 ) compared to that of the dark reaction (17 mW cm −2 ) [85]. Copper indium sulfide (CuInS 2 ) has also been used as photocathode in a dual-chamber PE-BFC.…”
Section: Materials Used In Pe-bfcmentioning
confidence: 99%
“…It was reported that LiNbO 3 cathodes exhibited a maximum power of 131 mW m −3 under irradiation and a maximum chemical oxygen demand (COD) removal of 84% [ 9 ]. In another study, LiTaO 3 , a ferroelectric material, has shown good performances as a photocathode with a maximum generated power of 55 mW m −3 and a COD removal power of 66% [ 18 ]. The electrocatalytic performance of ceramic materials, such as (Li 0 .…”
Section: Introductionmentioning
confidence: 99%